Risk, reconviction and their relationship to key developmental variables in a complete urban sample of child molesters and rapists - Craissati, Jackie (2003)
A good deal of attention has been paid to the question of recidivism in sex offenders, with a particular emphasis on identifying those variables which might best predict future risk. Despite growing interest in developmental variables, such as attachment and trauma, their relationship to risk in sex offenders has not yet been established. The aim of this thesis was to establish the extent to which developmental variables may contribute to a risk assessment model in sex offenders- based on fixed variables with particular reference to treatability and failure in the community. A complete urban sample of 310 convicted sex offenders (child molesters and rapists) were studied, and followed up after an average period at risk in the community of four years. It was found that key developmental variables - childhood victimisation (sexual, physical and emotional), emotional/behavioural difficulties, and insecure attachments to primary caregivers - were significantly associated with a higher risk of recidivism and treatment non-compliance. An enhanced prediction model is proposed, which postulates that the presence of a combination of two or three of these key developmental variables - considered in conjunction with a static risk prediction level - is the key to determining risk of community failure